Performance of general health workers in leprosy control activities at public health facilities in Amhara and Oromia States, Ethiopia. Issue 1 (December 2016) - Abeje, Tadiye; Negera, Edessa; Kebede, Eshetu; Hailu, Tsegaye; Hassen, Ismaile; Lema, Tsehainesh; Yamuah, Lawrence; Shiguti, Birru; Fenta, Melkamu; Negasa, Megersa; Beyene, Demissew; Bobosha, Kidist; et al.
Abstract Background Leprosy is a chronic infectious disease of public health importance and one of the leading causes of permanent physical disability. Nevertheless, the drop in prevalence following multidrug therapy has resulted in the neglect of leprosy. The annual incidence of leprosy has remained the same in Ethiopia since decades with more than 76 % of the reported new cases coming from Oromia and Amhara Regional States. This study was aimed to assess the knowledge, attitude and skill of general health workers in leprosy control activities at public health facilities in Oromia and Amhara Regional States. Methods A cross-sectional study was conducted from September 2011 to February 2012 at different public health facilities in selected eight zones in Oromia and Amhara Regional States. A multistage sampling method was used to obtain representative samples. High and low endemic zones for leprosy were included in the study in both regional states. Data were collected from general health workers through a structured self-administered questionnaire and at on-site assessment of their performance. Baseline socio-demographic data, health workers' attitude towards leprosy and their knowledge and skill in the management of leprosy were assessed. Bloom's cut off point was used to describe the knowledge and practical skills of the respondents while Likert's scale was used for attitude assessment. Result A total of 601 general health workers responsible for leprosy control activities at public health facilities were included in knowledge and attitude assessment and 83 of them were subjected to practical evaluation, with on-site observation of how they handle leprosy patients. These included medical doctors (4 %), health officers and nurses with Bachelor degree in Science (27 %), clinical nurses with diploma (66 %) and health assistants (2.8 %). The median age of the respondents was 26.0 years and females made up of 45 %. Generally the knowledge and skills of the respondents were found to be poor while attitude towards leprosy was positive for the majority of the respondents. The result showed that 519 (86.3 %) had poor knowledge. Overall 155 (25.8 %) of the respondents had positive attitude towards leprosy while 205 (34.1 %) had intermediate (mixed) attitude and 241 (40.1 %) had negative attitude to the disease. Among 83 respondents assessed for diagnosis of leprosy only 15(18.0 %) diagnosed leprosy correctly. Variation in knowledge and attitude indicated a significant difference (p  < 0.05) among different health institutions, professions, gender, in-service training and years of experience. Conclusion The current finding underlines that although leprosy control activities are integrated to the general health services in the country, the knowledge and skills of leprosy diagnosis, treatment and management by health workers was unsatisfactory. Hence, attention should be given to develop training strategies that can improve health worker knowledge and promote better leprosy management at public health facilities. This could be achieved through pre-service and in-service training and giving adequate emphasis to leprosy related practical work and continuous follow- up.